A thing of beauty: Structure and function of insulin's "aromatic triplet". (19th September 2018) - Weiss, Michael A.; Lawrence, Michael C.
Abstract : The classical crystal structure of insulin was determined in 1969 by D.C. Hodgkin et al. following a 35‐year program of research. This structure depicted a hexamer remarkable for its self‐assembly as a zinc‐coordinated trimer of dimer. Prominent at the dimer interface was an "aromatic triplet" of conserved residues at consecutive positions in the B chain: Phe B24, Phe B25 and Tyr B26 . The elegance of this interface inspired the Oxford team to poetry: "A thing of beauty is a joy forever" (John Keats as quoted by Blundell, T.L., et al. Advances in Protein Chemistry 26:279‐286 [1972]). Here, we revisit this aromatic triplet in light of recent advances in the structural biology of insulin bound as a monomer to fragments of the insulin receptor. Such co‐crystal structures have defined how these side chains pack at the primary hormone‐binding surface of the receptor ectodomain. On receptor binding, the B‐chain β‐strand (residues B24‐B28) containing the aromatic triplet detaches from the α‐helical core of the hormone. Whereas Tyr B26 lies at the periphery of the receptor interface and may functionally be replaced by a diverse set of substitutions, Phe B24 and Phe B25 engage invariant elements of receptor domains L1 and αCT. These critical contacts were anticipated by the discovery of diabetes‐associated mutations at these positions by Donald Steiner et al. at the University of Chicago. Conservation of Phe B24, Phe B25 and Tyr B26 among vertebrate insulins reflects the striking confluence of structure‐based evolutionary constraints: foldability, protective self‐assembly and hormonal activity.